JUDUL ABSTRAK TIDAK TERCANTUM DALAM BAHASA INGGRIS - FAKHRUDDIN (NIM : 10213082), FALAH
Heptazethrene Triisopropylsilyl (HZ-TIPS) is a derivative compound from Zethrene, which has seven sextet benzenoid rings that form a pattern of the letter Z. Heptazethrene has a uniques in its ground state conditions. There are two ground state condition can be owned by heptazethrene, the first is quinoidal closed shell and the second is biradical open shell. Both of these ground states can be generated by the synthesis method of heptazethrene itself. Heptazethrene with ground state of quinoidal closed shell has a stable ground state, which become known as Heptazethrene triisopropylsilyl (HZ-TIPS). This compound is what will be a discussion on this research. HZ-TIPS has a band gap energy about 1.4 eV which is in the range of infrared wavelengths, this behavior is different from the other organic materials in general, which has 1.5- 3 eV energy band gap which is in the range of UV-VIS wavelengrhs. These properties made HZ-TIPS become as the base materials candidate for optoelectronic device based on the absorption of infrared wavelength. In this study will be carried out about the optical constants characterization of thin film HZ-TIPS, which has grown on Highly Oriented Pyrolitic Graphite (HOPG) substrate. For the characterization was using spectroscopy ellipsometry to obtain a dielectric coefficient which is a characteristic of the optical properties posessed by the material. The dielectric function that was obtained from thin film HZ-TIPS on HOPG shows the appearance of electron-hole interaction between substrate and the thin film. This matter has review with comparing the dielectric function between tin film HZ-TIPS on SiO2. The effect of transferred electron make the HZ-TIPS on HOPG bacome more conductive. This conductive properties make the material become the candidate as active layer component on Organic Field Effect Transistor (OFET) device.